Two-dimensional free-surface flow under gravity: A new benchmark case for SPH method - J. Z. Wu; L. Fang (AIP Advances, 2018)
Currently there are few free-surface benchmark cases with analytical results for the Smoothed Particle Hydrodynamics (SPH) simulation. In the present contribution we introduce a two-dimensional free-surface flow under gravity, and obtain an analytical expression on the surface height difference and a theoretical estimation on the surface fractal dimension. They are preliminarily validated and supported by SPH calculations.